"Practical" Electrospinning of Biopolymers in Ionic Liquids. Issue 1 (6th December 2016) - Shamshina, Julia L.; Zavgorodnya, Oleksandra; Bonner, Jonathan R.; Gurau, Gabriela; Di Nardo, Thomas; Rogers, Robin D.
Abstract: To address the need to scale up technologies for electrospinning of biopolymers from ionic liquids to practical volumes, a setup for the multi‐needle electrospinning of chitin using the ionic liquid 1‐ethyl‐3‐methylimidazolium acetate, [C2 mim]‐[OAc], was designed, built, and demonstrated. Materials with controllable and high surface area were prepared at the nanoscale using ionic‐liquid solutions of high‐molecular‐weight chitin extracted with the same ionic liquid directly from shrimp shells. Abstract : Spinning round and round : A setup for multi‐needle electrospinning of the biopolymer chitin using the ionic liquid 1‐ethyl‐3‐methylimidazolium acetate is developed to realize electrospinning on a large scale. Biopolymers are relevant as a sustainable platform to potentially replace synthetic, non‐biodegradable plastics. The scale‐up of electrospinning from ionic liquids, which is demonstrated for chitin and shows potential for satisfying some requirements of industrial production, can be applied for virtually any biopolymer soluble in ionic liquids.